Major familial challenges in Malaysia: empirical findings and fiqh-based solutions = التحديات الأسرية ال كبرى في ماليزيا: نتائج تجريبية وحلول فقهية - Karim, Fatimah; Muhsin, Sayyed Mohamed (IIUM Press, 2025)
Muslim families in Malaysia face growing challenges stemming from modernization, digital disruption, economic pressures, and secular influences. These shifts have contributed to increasing marital conflict, parental neglect, intergenerational tensions, and erosion of religious values. While public discourse often emphasizes psychological and ethical reform, there remains an urgent need for concrete juristic responses rooted in the Islamic legal tradition. This study integrates classical fiqh rulings with empirical findings from a field survey involving 67 IIUM staff, who assessed key family-related challenges and the relevance of principles such as Wasatiyyah and Islamicization of the Self. Framed within the objectives of Islamic law (maqāṣid al-sharīʿah), the analysis highlights how Islamic jurisprudence provides structured legal tools—such as fasakh, ḥaḍānah, ṣulḥ, and taʿzīr—to preserve dignity, ensure justice, and restore family harmony. The study affirms that fiqh, when guided by moderation and ethical awareness, remains an adaptable and authoritative framework for addressing contemporary familial disruptions.